Essays on international financial integration and the financial sector - Carvalho, Daniel (Trinity College (Dublin, Ireland). Department of Economics, 2016)
This dissertation encompasses four essays, which deal with issues related to the cross-border financial integration and the financialization of economies. The first essay analyses whether foreign bond buying of euro area securities had an impact on euro area long-term interest rates. Capital flows into the euro area were particularly large in the mid-2000s and the share of foreign holdings of euro area securities increased substantially between the introduction of the euro and the outbreak of the global financial crisis. The essay shows that the increase in foreign holdings of euro area bonds in this period is associated with a reduction of euro area long-term interest rates by about 1.55 percentage points, which is in line with previous studies that document a similar impact of foreign bond buying on US Treasury yields. These results are relevant both from a euro area and a global perspective, as they show that the phenomenon of lower long-term interest rates due to foreign bond buying is not exclusive to the United States and foreign inflows into euro area debt securities may have added to increased risk appetite and hunt-for-yield at the global level. The second essay studies the composition of cross-border flows and their relationship with credit and money aggregates. While previous studies have focused on the relationship between international capital flows and domestic credit growth, highlighting the importance of the equity/debt mix, this chapter shows that there are also important implications of flows going to different domestic recipient sectors, especially concerning money dynamics. In particular, cross-border banking flows display a strong comovement with credit but none with broad money; in turn, flows of domestic non-banks display comovement with both credit and money. For this reason, banking flows correlate with the decoupling of these two variables – the Great Leveraging –, a stylised fact documented for several economies in the past decades and associated to the rapid expansion of banks non-monetary liabilities. These results thus shed light on the mechanisms through which the international banking activity might have consequences for the composition of the domestic bank balance sheet. The third essay looks at the interaction of financial flows and asset prices dynamics and how they contribute to shaping sectoral balance sheets and leverage for a set of OECD plus a few other mostly European countries. While debt instruments exhibit small holding gains and losses, equity instruments are subject to significant asset price changes. Importantly, these equity holding gains and losses display a significant positive comovement with investment in debt instruments. These patterns imply that, overall, favourable price valuations go hand in hand with the active build up of debt (and vice-versa), as well as tend to mask the increase in leverage when one considers measures based on market prices. Furthermore, this relationship is distinct across different sectors and financial corporations are the main drivers of this procyclical behaviour. Finally, the fourth essay establishes how financial accounts data allow for the computation of interlinkages across financial sectors and document how intra-financial assets of financial corporations have been growing considerably in recent times in a set of mostly advanced economies. How is this increase in financial sectors interconnectedeness associated with credit provided to end-user non-financial sectors? While intra-financial assets growth displays no significant comovement with credit provided to non-financial corporations and the general government, it does with credit provided to households. Moreover, this relationship stems mostly from claims among non-bank and across non-bank and bank financial corporations, and not from intra-bank claims. These results suggest that the expansion of the financial corporations’ interlinkages has been mostly associated with residential mortgages and consumption lending which, through activities such as securitization, contribute to the growth of links across the different financial sectors. Finally, general conclusions from this dissertation are presented in the last chapter.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin